Sex-Bias in Irritable Bowel Syndrome: Linking Steroids to the Gut-Brain Axis - So, Sik Yu; Savidge, Tor C. (Frontiers in Endocrinology, 2021)
Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder that is more common in females. Despite its high global incidence, the disease mechanism is still unclear and therapeutic options remain limited. The sexual dimorphism in IBS incidence suggests that sex steroids play a role in disease onset and symptoms severity. This review considers sex steroids and their involvement in IBS symptoms and the underlying disease mechanisms. Estrogens and androgens play important regulatory roles in IBS symptomology, including visceral sensitivity, gut motility and psychological conditions, possibly through modulating the gut-brain axis. Steroids are regulators of hypothalamic-pituitary-adrenal activity and autonomic nervous system function. They also modulate gut microbiota and enteric nervous systems, impacting serotonin and mast cell signaling. Sex steroids also facilitate bidirectional cross-talk between the microbiota and host following bacterial transformation and recycling of steroids by the intestine. The gender-specific interplay between sex steroids and the host provides neuroendocrinology insight into the pathophysiology, epigenetics and treatment of IBS patients.